A novel role for milk fat globule‐EGF factor 8 protein (MFGE8) in the mediation of mouse sperm–extracellular vesicle interactions. Issue 13 (9th May 2021) - Trigg, Natalie A.; Stanger, Simone J.; Zhou, Wei; Skerrett‐Byrne, David A.; Sipilä, Petra; Dun, Matthew D.; Eamens, Andrew L.; De Iuliis, Geoffry N.; Bromfield, Elizabeth G.; Roman, Shaun D.; Nixon, Brett
Abstract: Spermatozoa transition to functional maturity as they are conveyed through the epididymis, a highly specialized region of the male excurrent duct system. Owing to their transcriptionally and translationally inert state, this transformation into fertilization competent cells is driven by complex mechanisms of intercellular communication with the secretory epithelium that delineates the epididymal tubule. Chief among these mechanisms are the release of extracellular vesicles (EV), which have been implicated in the exchange of varied macromolecular cargo with spermatozoa. Here, we describe the optimization of a tractable cell culture model to study the mechanistic basis of sperm–extracellular vesicle interactions. In tandem with receptor inhibition strategies, our data demonstrate the importance of milk fat globule‐EGF factor 8 (MFGE8) protein in mediating the efficient exchange of macromolecular EV cargo with mouse spermatozoa; with the MFGE8 integrin‐binding Arg‐Gly‐Asp (RGD) tripeptide motif identified as being of particular importance. Specifically, complementary strategies involving MFGE8 RGD domain ablation, competitive RGD‐peptide inhibition and antibody‐masking of alpha V integrin receptors, all significantly inhibited the uptake and redistribution of EV‐delivered proteins into immature mouse spermatozoa. These collective data implicate the MFGE8 ligand and its cognate integrin receptor in the mediation of the EV interactions that underpin sperm maturation.